PEMETAAN ZONA POTENSIAL PENANGKAPAN IKAN BERDASARKAN CITRA SATELIT AQUA/TERRA MODIS DI PERAIRAN SELATAN PULAU JAWA - Munthe, Masri Ginting; Jaya, Yales Veva; Putra, Risandi Dwirama (Dinamika Maritim, 2018)
Remote sensing is technique to observe oceanographic parameters such as sea surface temperature and chlorophyll-a concentration without contact with objects. Remote sensing techniques have excellence ability in analyzing large area and resolve to take retrieval data is more efficient. Remote sensing can combined with geographical information system to determine the potential fishing zone (ZPPI). The southern sea of Java Island is potential fishing areas in Indonesia. The purpose of this study to determine potential fishing zone by observe condition the seas which habitat species using the parameters of sea surface temperature (SPL) and chlorophyll-a concentration (CHL) parameters. Sea surface temperature and chlorophyll-a concentration are important parameters for identify potential fishing zones. The method used in study analysis of sea surface temperature and chlorophyll-a concentration using AQUA/TERRA MODIS satellite imagery data processed on ENVI, ErMapper, and ArcGIS software. The sea of South Java are 166 potential fishing zones. spread evenly from Banten to East Java it can be conclude that the southern sea of Java Island are still in good condition and deserve to be potential fishing zone.